Organizational effectiveness of data centers: A foundation for effective cloud architectures - Ajay Ahuja (The International Journal of Management Science and Information Technology (IJMSIT), 2016)
Information Technology (IT) is integral to our day-to-day life and IT trends are dynamic and evolving. With an aim towards operational and technical excellence, Enterprises are moving towards Cloud enabled IT architectures. Various business and operational models are being evaluated and many global Enterprises have already started using Cloud based solutions. The fact remains - all of these Cloud enabled solutions are hosted out of Data Centers. Data Centers are setups within an IT organization, where servers, storage, networking and IT management equipment are hosted to provide IT enabled services to the end-users. Data Centers are like sub organizations within an IT organization. Cloud enabled architectures for different Cloud models are configured on a set of IT equipment hosted out of these Data Centers. Therefore, Effectiveness and Efficiency of these Data Centers is absolutely essential for effectiveness and efficiency of Cloud enabled IT services. Effectiveness of Data Center organizations is therefore an important and crucial aspect of Cloud architectures. This paper presents various factors and measures that contribute to Organizational Effectiveness of Data Centers - a foundation for an effective Cloud architecture. These factors and measures may be used as a foundational framework to be referred by the global Enterprises, who are moving towards an effective Cloud architecture. The findings are applicable to all such enterprises across private and public sector domains.
Keywords: 650; Data Centers; Cloud Architectures; Organizational Effectiveness